2023
DOI: 10.1111/cas.15870
|View full text |Cite
|
Sign up to set email alerts
|

Splicing factor TRA2A contributes to esophageal cancer progression via a noncanonical role in lncRNA m6A methylation

Abstract: Transformer 2 alpha homolog (TRA2A), a member of the serine/arginine-rich splicing factor family, has been shown to control mRNA splicing in development and cancers. However, it remains unclear whether TRA2A is involved in lncRNA regulation. In the present study, we found that TRA2A was upregulated and correlated with poor prognosis in esophageal cancer. Downregulation of TRA2A suppressed the tumor growth in xenograft nude mice. Epitranscriptomic microarray showed that depletion of TRA2A affected global lncRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…have reported that m 6 A sites are enriched in exonic regions flanking 5′- and 3′-splice sites, that overlap with the ESE binding regions, suggesting that m 6 A signals may be related to the activity of SR proteins [ 101 ]. Further supporting this point, we and others recently found that several SR proteins, including TRA2A, SRSF3, and SRSF7, can interact with METTL3 and other proteins in RNA methylation, and the m 6 A signal in pre-mRNA is essential for SR proteins to participate in RNA processing [ 94 , 96 , 98 , 102 ].…”
Section: Functional Mechanisms Of Sr Proteins In Cancermentioning
confidence: 57%
See 2 more Smart Citations
“…have reported that m 6 A sites are enriched in exonic regions flanking 5′- and 3′-splice sites, that overlap with the ESE binding regions, suggesting that m 6 A signals may be related to the activity of SR proteins [ 101 ]. Further supporting this point, we and others recently found that several SR proteins, including TRA2A, SRSF3, and SRSF7, can interact with METTL3 and other proteins in RNA methylation, and the m 6 A signal in pre-mRNA is essential for SR proteins to participate in RNA processing [ 94 , 96 , 98 , 102 ].…”
Section: Functional Mechanisms Of Sr Proteins In Cancermentioning
confidence: 57%
“…Recently, we have demonstrated that TRA2A induces esophageal cancer progression via MALAT1 [ 97 ]. Mechanistically, TRA2A directly interacts with core methyltransferase METTL3 and the m 6 A reader RBMX to regulate the methylation and stability of MALAT1 [ 98 ].…”
Section: Functional Mechanisms Of Sr Proteins In Cancermentioning
confidence: 99%
See 1 more Smart Citation